Role of UHMWPE in Knee Transplant (International Journal of Advanced Research in Science, Management and Technology, 2016)
Tibial Insert, a plastic layer between the femoral and tibial plate plays an important role in the functioning of knee. Femoral slides on the tibial insert whenever the knee is bent or straightened or in action. As the femoral is a metallic component, the tibial insert should provide less friction. And also considering the objective of minimising the wear rate of the knee transplant, tibial insert is made up of biocompatible material. Ultra high molecular weight polyethylene (UHMWPE) is a very tough material with highest impact strength of any thermoplastic presently made and is finding wide applications in every field including automobile industries, bottling sectors and medical field. The properties of UHMWPE is favouring to be used in medical devices as it is self-lubricating with less coefficient of friction and minimal moisture absorption. The formation of UHMWPE and processing should be carried out with utmost care as the method of producing has direct impact on the wear. The recommended grade of UHMWPE required for medical and manufacturing method of tibial insert is justified.
Keywords: UHMWPE, Tibial insert, Knee Transplant